STUDENTS’ABILITY IN TRANSLATING BUSINESS LETTER FROM ENGLISH INTO INDONESIAN AT ENGLISH DEPARTMENT OF BUNG HATTA UNIVERSITY - Lailatul Husna; Nadira Arindra Rahma Eisya (English Language Education and Current Trends (ELECT), 2022)
This research was aimed to describe the fourth year students’ ability in translating a business letter from English into Indonesian at the English Department of Bung Hatta University. The design of this research was descriptive. The research sample members were 20 students chosen by using total sampling techniques. The data were collected through a Translation Testand analysed by using a descriptive statistics. The result of data analysis showed the students had very good ability in translating a business letter from English into Indonesian. Furtherly, it can be explained that the students had  very good ability in using lexical equivalence in translating a business letter.While, the students’ ability in using grammatical adjustment in translating a business letter was good. Based on the result of this research, it can be concluded that the fourth year students’ ability in translating a business letter from English into Indonesian at the  English Department of Bung Hatta University was very good. And further research is needed to do to find the reason why the students’ ability in using grammatical adjustment in translating a businessletter from English into Indonesian was not very good either.   REFERENCES Al-Darawish, H. (1983). Arabizing University Education in Arabic, Jerusalem, Arab Studies Society.Cited in Hamdallah, R., Problems and Approaches to Translation With Reference To Arabic.Language and translation.J.King Saud University, 10.23-38. Arono, Nadrah (2019), Students’ Difficulties in Translating English Text.Journal of Applied Linguistics and Literature 4 (1). Ashley, A. 2008.Oxford Handbook of Commercial Correspondence with Workbook.New York: Oxford University Press. Basnett, S. (2002).Translation Studies: (3rd ed.). New York: Routledge. Budianto and Fardhani. 2010. A Practical Guide for Translation Skill. Malang: UINMALIKI Press. Choliludin. 2006. The Technique of Making Idiomatic Translation. Jakarta: Kesaint Blanc. Duff, Allan. (1989). Translation. London: Oxford University Press. Fikra.(2014). An Analysis of The Fourth Year Students’ Ability of English Department at Bung Hatta University in Translating “Job Vacancy Text” from English into Indonesian.Unpublished thesis. Padang: Bung Hatta University. Jalilifar, Beitsayyah (2011), Genre Analysis of Enquiry Letters Across Cultures: Perspectives on Rhetorical Structures. Jothiraj (2004). Translation as transcreation: problems and prospects. Thesis. Department of English, University of Calicut. Machan, T. William. 1997. English in the Middle Ages. Oxford: Oxford University Press. Mortezapour, Akbar. 2008. A Handbook of Correspondence. Tehran: Atar Publication Nababan et al (2012). Pengembangan Model Penilaian Kualitas Terjemahan. Universitas Sebelas Maret Surakarta. Newmark, P. (2008). A Textbook of Translation. London: Prentice-Hall International (UK) Ltd. Newmark, P. (1988). A Textbook of Translation. London: Prentice-Hall International Ordudari (2007).Translation Procedures, Strategies and Methods.Translation Jurnal, 11 (3). Silva (2017). Jakobson’s Intersemiotic Translations in Asterix Comics. Comparatismi 1I Soemantri, Marjito (2011). An Analyzing Students’ Performance in Translating Abstract from Indonesia into English.JurnalComputech&Bisnis, 5 (2), 103-114. Sudartini, S. (2009). The Question of Grammatical Equivalence in Translation. Journal of   English education, 3. Tanjung, S. (2015).PenilaianpenerjemahanJerman-Indonesia. Yogyakarta: Kanwa Publisher.